Using Toy Animal Ball Poppers to Explore Projectile Motion in Algebra and Calculus Classes - Guntharp, Marsha Nicol; Browning, Fred; Royle, Gloria (Ohio Journal of School Mathematics, 2017)
In this manuscript, we describe an activity that we have adapted for use with algebra and calculus students. By videotaping flying balls and then using an iPad app to track the flight for use in a TI-Nspire graphs page, students are encouraged to engage with the mathematics.